Association between non-alcoholic fatty liver disease and arterial stiffness measured by brachial-ankle pulse wave velocity: a cross-sectional population study - Yujie Wang; Zhicheng Fang; Qiuyue Fu; Dongai Yao; Xiaoqing Jin (PeerJ)
Background Non-alcoholic fatty liver disease (NAFLD) is strongly linked with metabolic syndrome and atherosclerotic cardiovascular diseases (ASCVDs). This study aimed to assess the feasibility of using brachial-ankle pulse wave velocity (baPWV), a non-invasive technique, to monitor atherosclerosis (AS) in NAFLD patients and to evaluate the AS risk in various sub-populations of NAFLD patients. Materials and methods A cross-sectional study was conducted with 4,844 participants, enrolled from January 1, 2019, to December 31, 2021, at the Physical Examination Center of Zhongnan Hospital of Wuhan University. Participants were aged 18 to 88 years. According to the main points of the ultrasonic diagnosis of NAFLD, the ultrasonic image report was made for the subjects. AS is defined as baPWV ≥ 1,400 cm/s. We used multiple logistic regression analysis to explore the relationship between NAFLD and AS, and multiple linear regression analysis to explore the correlation between NAFLD and baPWV by modeling. Subgroup analysis was performed based on age and gender to adjust for confounding bias and complete sensitivity analysis. Results The prevalence of NAFLD was 38.3% in all participants, with 45.4% in men and 25.1% in women. Among the overall NAFLD population and male NAFLD patients, baPWV exceeded the diagnostic threshold for AS (1,419.70 ± 205.51, 1,429.71 ± 196.13) starting from the 45–55 age group. Through the analysis of the age-baPWV scatter plots and fitted lines, along with sensitivity analysis, it is recommended that male patients should start monitoring at 46 years old for AS using baPWV, while female patients should begin at 51 years old. NAFLD was associated with increased odds of AS (OR: 1.206, 95% CI [1.021–1.423], P = 0.027) after adjusting for confounders. NAFLD was independently positively correlated with baPWV (Model 2: β = 0.086, ΔR2 = 0.006, P < 0.001; Model 3: β = 0.05, P < 0.001). This positive correlation was also observed in both males and females (male: Model 2: β = 0.081, ΔR2 = 0.005, P < 0.001; Model 3: β = 0.052, P = 0.001; female: Model 2: β = 0.088, ΔR2 = 0.006, P < 0.001; Model 3: β = 0.042, P = 0.02). Conclusion NAFLD demonstrated an independent association with AS assessed via baPWV, an accessible non-invasive tool for early AS evaluation. Regular baPWV monitoring is recommended for NAFLD patients > 45 years, with males and females initiating surveillance at 46 and 51 years, respectively. Study limitations, including potential biases in NAFLD diagnosis, gender distribution imbalances, and confounding variable interdependencies, necessitate further stratified population analyses.